Inertial parameter estimation for the dynamic simulation of a hydraulic excavator - Yoo, Seungjin; Park, Cheol-Gyu; You, Seung-Han (Journal of mechanical science and technology, 2018)
This paper presents a systematic method for estimating the inertial parameters of an excavator. The method utilizes dynamic excavator models with the pressure and displacement measurements of the hydraulic actuators. Provided that the geometrical parameters of the mechanical linkages are obtained with relatively high accuracy, the dynamic model is factored into the unknown inertial parameter vector and the known kinematic matrix. The contribution of each inertial parameter on the actuator force under the specific motion is explored through a dynamic sensitivity analysis. The results are then used to investigate various properties of the inertial parameters and categorize them into identifiable, unrelated to dynamics, and known parameter groups, according to numerical properties of the kinematic matrix. Then the identifiable inertial parameters are estimated sequentially, and the guideline for the optimal excavator position at each estimation step is suggested in order to minimize estimation error. The practicality of this method is demonstrated via data acquired using an actual hydraulic excavator.